Table of Content - - (Journal of natural sciences, life and applied sciences, 2025)
Table of Content: 1. Analysis of Morphometric Characteristics and Land Use in the Oued Tamri and Adoudou Watersheds, Morocco: A Spatial and Temporal Study Using GIS and Remote Sensing Dr. Soukaina Amrani 2. Modeling Topographic Variables in Relation to Land Cover and Land Use Changes in Hail City Lecturer Afaf Salem Al-Shammari ,Dr. Abdul-Rahman Suleiman Al-Nisayan 3. Maxwell’s Equations Under Lorentz Transformations: Investigating the Spontaneous Emergence of Magnetic Charge and Current Densities Mr. Louai Hassan Elzein Bashier